2016
DOI: 10.1126/scitranslmed.aag0367
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune manifestations in aged mice arise from early-life immune dysregulation

Abstract: Autoantibodies can be present years to decades prior to the onset of disease manifestations in autoimmunity. This suggests that the initial autoimmune trigger involves a peripheral lymphoid component, which ultimately drives disease pathology in local tissues later in life. Here we show Sjögren’s Syndrome manifestations that develop in aged NOD.H-2h4 mice were driven by and dependent on peripheral dysregulation that arose in early life. Specifically, elimination of spontaneous germinal centers in spleens of yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 82 publications
3
38
0
Order By: Relevance
“…In contrast, immune cells may become activated in the periphery and enter the salivary tissue stochastically in SS. Support for this scenario is provided by recent work in a related NOD model (NOD.H-2h4), demonstrating that blockade of CD40 ligand before disease onset abrogates splenic germinal center formation and prevents salivary gland inflammation and autoantibody production later in life [55]. Data from human studies provide support for the importance of early peripheral immune dysregulation in disease, as antibody production is reported to occur years before onset of salivary dysfunction in pSS patients [56,57].…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, immune cells may become activated in the periphery and enter the salivary tissue stochastically in SS. Support for this scenario is provided by recent work in a related NOD model (NOD.H-2h4), demonstrating that blockade of CD40 ligand before disease onset abrogates splenic germinal center formation and prevents salivary gland inflammation and autoantibody production later in life [55]. Data from human studies provide support for the importance of early peripheral immune dysregulation in disease, as antibody production is reported to occur years before onset of salivary dysfunction in pSS patients [56,57].…”
Section: Discussionmentioning
confidence: 93%
“…However, on this regimen there is no difference between sexes in the development of thyroid autoimmunity [9,10], for which reason later studies on NOD.H2 h4 mice involved either one sex or groups of mixed sex [11][12][13][14][15][16][17]. For Hashimoto's thyroiditis, NOD.H2 h4 mice are the most practical and commonly studied model.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these studies did not assess TPOAb, a more important marker than TgAb for autoimmune thyroiditis in humans. Consequently, although some investigations in NOD.H2 h4 mice focused on males [11] or females [12,13], many studies combined their observations for both sexes (for example [14,15] or reported their findings without providing mouse sex [16], as in one of our own studies [17]. With this experimental protocol, sexual dimorphism for thyroid autoimmunity has not been observed in NOD.H2 h4 mice, a major difference with human disease.…”
Section: Introductionmentioning
confidence: 99%
“…DCs from prediabetic NOD mice have increased CD40 expression that is dependent on adaptive immune cells. Increased CD40 expression could be more indicative of inflammation, as blocking CD40 signals blocks NOD autoimmune diabetes pathogenesis (145148). …”
Section: And Autoimmune Pathologies/diseasesmentioning
confidence: 99%